SISTEM UJIAN ONLINE SEBAGAI UPAYA PENINGKATAN PELAKSANAAN UJIAN DALAM PENDIDIKAN TERBUKA JARAK JAUH *) - Timbul Pardede; Sri Listyarini (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2011)
Universitas Terbuka (UT) as a higheropen anddistanceeducationinstitution has beencarrying outstudents assessmentin the form ofpaper and pencil and online examinations. This studywas conductedto determinethe effectiveness ofthe implementation of theOnline ExaminationSystem(Sistem Ujian Online=SUO), in terms of the reliability(robustness) of SUO application, the readiness ofHuman Resources inimplementingan online exam, the infrastructure that supporting SUO, and the studentresponses. The results showed that SUO applicationand support application had beenwell developedbyUT, proven that the SUO havebeenin operation in 30 out of 37UTregional centersin 2010. Studentsdid notface manyproblems in registering in the online exam.Infrastructureandhuman resourceswere considered satisfactory. Respondentsalso said that SUO was veryflexiblein terms of choosing theexamschedule andgetting the immediate feedback. Based on the research results, a SUO modelhad been developed and to be implementedatUT. The SUOmodel isdescribed inseveralbusinessprocesses, which includethe preparation, execution, processingexam results, as well assupervisionandevaluation. In the future, UTstillneeds toimprovefacilities, infrastructure andquality of human resources thatcansupport theonline exam. The implementation of online examrelies heavily oninformationtechnology (IT) and itis expectedthatSUOis adaptablewith this rapidly changed technology.